Tapping Into Rate Flexibility: Musical Training Facilitates Synchronization Around Spontaneous Production Rates - Scheurich, Rebecca; Zamm, Anna; Palmer, Caroline (Frontiers in Psychology, 2018)
The ability to flexibly adapt one's behavior is critical for social tasks such as speech and music performance, in which individuals must coordinate the timing of their actions with others. Natural movement frequencies, also called spontaneous rates, constrain synchronization accuracy between partners during duet music performance, whereas musical training enhances synchronization accuracy. We investigated the combined influences of these factors on the flexibility with which individuals can synchronize their actions with sequences at different rates. First, we developed a novel musical task capable of measuring spontaneous rates in both musicians and nonmusicians in which participants tapped the rhythm of a familiar melody while hearing the corresponding melody tones. The novel task was validated by similar measures of spontaneous rates generated by piano performance and by the tapping task from the same pianists. We then implemented the novel task with musicians and nonmusicians as they synchronized tapping of a familiar melody with a metronome at their spontaneous rates, and at rates proportionally slower and faster than their spontaneous rates. Musicians synchronized more flexibly across rates than nonmusicians, indicated by greater synchronization accuracy. Additionally, musicians showed greater engagement of error correction mechanisms than nonmusicians. Finally, differences in flexibility were characterized by more recurrent (repetitive) and patterned synchronization in nonmusicians, indicative of greater temporal rigidity.